2021
DOI: 10.4236/ojog.2021.115050
|View full text |Cite
|
Sign up to set email alerts
|

Educational Program for Pregnant Women Regarding Obstetrics Dangerous Signs in Rural Areas

Abstract: Background: Complications linked to postpartum & pregnancy are one of the major causes of female death. In order to understand the causes of complications and encourage women to take sufficient action in order to receive emergency treatment, a critical step should therefore be taken to minimize complications related to pregnancy, in order to ensure the safety of both women and newborns. Aim of the work: Evaluate the effectiveness of the education programs for pregnant women on obstetric danger signs in rural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Community-based HEI increased the likelihood of women's knowledge regarding ODS. Consistent results were reported from the studies done in Sokoto State, Nigeria [71], rural Egypt [72], Lagos State, Nigeria [73], Zagazig University Hospitals [74], Nicaragua [75], and Cairo University Hospitals [76]. The reason could be that most earlier studies revealed that advanced levels of education were linked to enhanced cognitive skills, improved information processing abilities, and better values, which help to increase knowledge [77][78][79].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Community-based HEI increased the likelihood of women's knowledge regarding ODS. Consistent results were reported from the studies done in Sokoto State, Nigeria [71], rural Egypt [72], Lagos State, Nigeria [73], Zagazig University Hospitals [74], Nicaragua [75], and Cairo University Hospitals [76]. The reason could be that most earlier studies revealed that advanced levels of education were linked to enhanced cognitive skills, improved information processing abilities, and better values, which help to increase knowledge [77][78][79].…”
Section: Discussionsupporting
confidence: 67%
“…However, evidence is lacking to comprehensively assess the effects of knowledge learned from HEI on MHSU. Thus, our studies in another paper evaluated whether this knowledge of ODS obtained from HEI might be changed into an increase in MHSU in a study setting similar to those observed following intervention in Nigeria [71], Egypt [72], and Nicaragua [75]. Thus, HEI could be a beneficial supplement to women's education in rural areas, increasing the utilization of MHS and preventing delays in emergency obstetric care.…”
Section: Discussionmentioning
confidence: 90%
“…The education program has effectively improved mothers' knowledge and practices regarding danger signs for pregnant women in rural areas, with highly statistically significant differences across all items tested between pre-and post-program implementation, with a value of (P < 0.001). (Gobran et al, 2021) 13.…”
Section: "Educational Program For Pregnant Women Regarding Obstetrics...mentioning
confidence: 99%
“…Other complications listed were miscarriage and abortion [4] [13], oedema and poor presentation [11] [12] [14] [16] [17]. In addition, prolonged labor [15] [17] and intrauterine fetal death [13] are also listed. Further, high frequencies of headache and fever have also been reported by some authors [10] [14] [17] as well as premature rupture of membranes [18].…”
Section: ) Knowledgementioning
confidence: 99%